Private food safety and quality standards: facilitating or frustrating fresh produce growers? - Baines, R.N,; Soon, J.M. (2013)
Global private food safety and quality standards have undergone some major overhauls over the past two decades with an increasing emphasis on harmonisation. The Global Food Safety Initiative (GFSI) benchmarking process is an efficient model to measure compliance which contributes to harmonising future food safety standards. While GFSI attempts to harmonise retail standards are commendable and elegant in principle, in practice, retailers continue to support their own standards. It is difficult to see retailers giving up on their own standards and the control they currently exert as chain captains. Although there are advantages in harmonising the standards and reducing certification costs, there is a need to ensure inspection costs are competitive. There is also the risk that too much harmonisation will result in private standards losing their individuality and uniqueness. Amidst the struggle for private standard dominance, alternative approaches to risk management are emerging in a similar way to how insurance risks are calculated for business. As such, certification of standards could disappear in favour of a more general risk and insurance model. This risk based approach could also lead to the effective implementation of co-regulation, where both public and private sector compliances are addressed together. This paper reviews the public-private food standards trend over the past 20 years, considers the implications and future trends in cultivating fresh produce, especially for smallholder farmers, and explores the possibility of co-regulatory coordination between publicprivate sectors and the potential of a risk-based insurance model for food and farming